1991
DOI: 10.1161/01.hyp.18.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise hypotension is not sustained in normal and hypertensive humans.

Abstract: Blood pressure falls after a single session of exercise. The duration for which this fall in blood pressure persists is not known. Sustained hypotension after a single session of exercise may have important implications in the treatment of patients with mild hypertension. We studied 24 subjects (12 normotensive subjects and 12 patients with mild or borderline hypertension). Blood pressure was measured in the laboratory for 30 minutes before and for an hour after graded bicycle exercise to maximal voluntary cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
1
18

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 17 publications
9
52
1
18
Order By: Relevance
“…10,11,19,22,24,[31][32][33]35,41,[43][44][45][59][60][61]63,71,72 Treadmill exercise at similar intensities has also been documented to elicit PEH. 14,15,20,25,34,40,[55][56][57][58] Direct comparisons of the effect of exercise intensity have, for the most part, found that PEH occurs independent of exercise intensity.…”
Section: Intensity Of the Exercisementioning
confidence: 99%
See 3 more Smart Citations
“…10,11,19,22,24,[31][32][33]35,41,[43][44][45][59][60][61]63,71,72 Treadmill exercise at similar intensities has also been documented to elicit PEH. 14,15,20,25,34,40,[55][56][57][58] Direct comparisons of the effect of exercise intensity have, for the most part, found that PEH occurs independent of exercise intensity.…”
Section: Intensity Of the Exercisementioning
confidence: 99%
“…9,16,31,44,49,57,61 Most studies have measured blood pressure for only 1-2 h following exercise 12,13,16,20,22,23,25,34,[36][37][38][39]55,58,75 and the majority of these have found a nadir in blood pressure during that time with a return or trend towards baseline pressure at the cessation of measurement.…”
Section: Duration Of the Responsementioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7][8][9][10] Treadmill exercise at similar intensities has also been shown to elicit PEH. Direct comparisons of the effect of exercise intensity on PEH have been limited to 40 and 70% of maximal exercise.…”
Section: Introductionmentioning
confidence: 99%